Fuzzy logic: An instrument for the evaluation of project status - Radek Doskéocil (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2015)
This article considers the use of fuzzy logic to support the evaluation of project status. A brief description of fuzzy set theory, fuzzy logic and the process of calculation is given. The major goal of this paper is to present an expert decision-making fuzzy model for evaluating project status. The model results from the application of the Fuzzy Logic Toolbox. This fuzzy model is based on two basic indices, schedule performance index (SPI) and cost performance index (CPI), of earned value management (EVM). The ad- vantage of the fuzzy model is the ability to transform the input indices SPI and CPI into linguistic variables, as well as linguistic evaluation of over- all project status (output). With this approach it is possible to simulate the risk and uncertainty that are always associated with real projects. The scheme of the model, rule block, attributes and their membership functions are mentioned in a case study. The case study contains real data on the development of values of indices SPI and CPI for one project in the field of IT (data file). The analysed project ran from March 2012 to July 2012. The indices SPI and CPI were obtained from control project milestones. There are 5 control milestones in total. The parameters of the model are adjusted on the basis of the data file for each of the variables. The use of fuzzy logic is a particular advantage in decision-making processes where description by algorithms is extremely difficult and criteria are multiplied.
Keywords: C44; M19; M21; 330; project management; earned value management (EVM); soft computing; fuzzy logic; decision-making